2015
DOI: 10.1039/c5cy00700c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of 2,5-dihydroxymethylfuran and 2,5-dimethylfuran from 5-hydroxymethylfurfural using mineral-derived Cu catalysts as versatile catalysts

Abstract: Selective conversion of 5-hydroxymethylfurfural (HMF) can produce sustainable fuels and chemicals.Herein, Cu-ZnO catalysts derived from minerals (malachite, rosasite and aurichalcite) were employed for selective hydrogenation of HMF for the first time. High yields of 2,5-dihydroxymethylfuran (~99.1%) and 2,5-dimethylfuran (~91.8%) were obtained tunably over the catalyst with a Cu/Zn molar ratio of 2, due to the well-dispersed metal sites tailored by mineral precursors, well-controlled surface sites and optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(98 citation statements)
references
References 44 publications
3
95
0
Order By: Relevance
“…The structures of the synthesized samples could also be demonstrated by Raman spectra shown in Figure (c). The band at 1070 cm −1 corresponds to the CO 3 2− symmetric stretching mode of aurichalcite whereas the peaks at 1100 cm −1 , 1370 cm −1 and 1500 cm −1 can be assigned to the zincian malachite phase . Based on the results of XRD patterns and Raman spectra, the synthesized samples were verified to be the presupposed precursors that mainly consisted of aurichalcite and zincian malachite, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…The structures of the synthesized samples could also be demonstrated by Raman spectra shown in Figure (c). The band at 1070 cm −1 corresponds to the CO 3 2− symmetric stretching mode of aurichalcite whereas the peaks at 1100 cm −1 , 1370 cm −1 and 1500 cm −1 can be assigned to the zincian malachite phase . Based on the results of XRD patterns and Raman spectra, the synthesized samples were verified to be the presupposed precursors that mainly consisted of aurichalcite and zincian malachite, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…If THF was used as the solvent, only 34.7 %y ield of the target product DMF was obtained after 12 h. MF was observeda st he major byproduct, achievingamaximumy ield of 60.6 %a t6h and then decreasing gradually.T his product distribution demonstrated that the reaction rate of the HDO of HMF to MF was much highert han that of the HDO of MF to DMF,l eadingt o the accumulationo fM Fi nt he solution. [42] The HDO of MF andM FM overF e/C-800 in n-butanolw as explored to investigate the role of FeN x species in the HDO of C=Oa nd CÀOb onds (see FigureS5).T he DMF yields were 44 and 53 %f or the HDO of MF andM FM, respectively.T he inferior catalytic performance demonstrated thatt he presence of FeN x species was critical for both HDO reactions. If n-butanol was used as the solvent, the productionr ate of DMF was enhanced significantly,a nd am aximum yield of 86.2 %w as obtained within 5h.M Fa chieved am aximum yield of 9.9 %a t 1h and was then converted completely after 6h.I na ddition, DFF,w hich is the dehydrogenation product of HMF,a chieved am aximum yield of 4.4 %i nT HF but could not be detected with n-butanol as the solvent.…”
Section: Reaction Pathwaysmentioning
confidence: 99%
“…[32] Considering the high cost and scarcityo fn oble metals, the HDO of HMF to DMF over non-noble-metal catalysts was investigated recently.T he activities and stabilities of six carbon-supported noble-o rn on-noble-metalc atalysts were comparedi n ac ontinuous-flow reactor by Gorte and co-workers. [39][40][41][42] They also studied the one-step continuous conversiono ff ructoset o DMF over combined HY zeolite and HT-Cu/ZnO/Al 2 O 3 in af ixed-bed reactor with aD MF yield of 40.6 %. [34] Subsequently,t hey studied the conversion of HMF over Cu 0.61 Mg 2.33 Al 0.98 Ru 0.02 and CuÀZn nanoalloy catalysts, and up to 97 %c ombined product yields were obtained at 200-220 8Ca nd 20-30 bar H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al . reported the synthesis of 2,5‐dihydroxymethylfuran and 2,5‐dimethylfuran from 5 hydroxymethylfurfural using Cu–ZnO as catalysts . Nagpure et al .…”
Section: Introductionmentioning
confidence: 99%